A prospective randomized controlled trial comparing the immediate post-operative complications between open and semi-open hemorrhoidectomy - Rijal, Bhuban; Basnet, Robin Bahadur (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Hemorrhoids are one of the most common anorectal pathologies encountered by general surgeons during their practice. Open technique as described by Milligan and Morgan and closed technique as described by Ferguson are the most widely used. A semi-open technique that has lesser complications than the conventional open hemorrhoidectomy has been described. This study aims to compare the immediate postoperative complications between open and semi-open hemorrhoidectomy. Methods: A prospective randomized study, where patients with third and fourth-degree hemorrhoids undergoing hemorrhoidectomy, were taken for the study. The subjects were randomized into two groups, where they underwent either open or semi-open hemorrhoidectomy. Both groups received standard postoperative care and were evaluated after 24 hours after surgery for pain and urine retention and were then discharged with the same treatment plan for both groups. First, follow up was done in one week and the second was done in two weeks after discharge, where pain score, bleeding, wound healing, use of narcotic analgesics and patient discomfort were recorded. Results: A total of 44 patients were divided into two groups, where the age, sex, and grade of hemorrhoids were matched. The pain score using VAS in the first week was compared and it showed that the pain perceived by the patients in the open hemorrhoidectomy was greater than in the semi-open method ((p=0.06, 95% CI= 0.22 to 1.23). Bleeding rate after the surgeries were not different between the two groups (p=0.43) and the urinary retention between them was also not significant (p=0.47). The use of breakthrough narcotic analgesics was more in the open hemorrhoidectomy group (p=0.01). On the fourteenth day follow up, the wound of those who underwent semi-open hemorrhoidectomy, had significantly healed as compared to those who had undergone the open procedure (p= 0.04, 95% CI=0.23 to 0.76), and the patients who had semi-open hemorrhoidectomy had lesser discomfort as compared to the open technique (p=0.02). Conclusion: Semi-open hemorrhoidectomy has fewer post-operative complication rates as compared to open hemorrhoidectomy with decreased pain, faster wound healing rates, and lesser patient discomfort.